Targeted therapies in multiple myeloma - Kastritis, E.; Charidimou, A.; Varkaris, A.; Dimopoulos, M.A. (Targeted Oncology, 2009)
Increasing knowledge of the biology of multiple myeloma led the way for the development of novel drugs that have changed the management of the disease. New treatments target not only to the malignant plasma cell but also target the interactions of myeloma cells with their microenvironment. Several preclinical studies have identified potential targets and drugs are developed that act on pathways crucial for myeloma cell survival, proliferation, migration and drug resistance. The identification of active agents in the laboratory is followed by rationally designed clinical studies that validate these drugs, either as single agents or in combinations with other active drugs. These novel agents may be either small molecules or monoclonal antibodies targeting receptors, kinase activity of receptors or key molecules within critical pathways, intracellular maintenance mechanisms and immune modulation. © 2009 Springer-Verlag.
Keywords: Angiogenesis; Bcl-2; Heat shock protein 90 inhibitors; Histone deacetylase inhibitors; IMiDs; Lenalidomide; mTOR; pomalidomide; Proteasome inhibitors; Thalidomide